Dynamic response analysis of monorail steel-concrete composite beam-train interaction system considering slip effect. (1st April 2018) - Wang, Hongliang; Zhu, Eryu
Highlights: A new model of steel-concrete composite beam considering slip effect is proposed. Dynamic analysis procedure considering slip effect is established. Slip effect on dynamic responses of monorail composite beam-train is proposed. Critical value (0.8 × 10 6  N/m) of the connect stiffness exists in composite beams. Abstract: A new finite element model of steel-concrete composite beam which can simulate the slip phenomenon is proposed in this paper. The new model consists of concrete beam unit, shear connector unit and steel beam unit. Based on the improved model, a new steel-concrete composite track beam-train interaction system is derived for the dynamic analysis. Each vehicle of monorail train in the new steel-concrete composite track beam-train interaction system is idealized as a multi-body system with 18 degrees of freedom. The governing vibration equations of the new monorail steel-concrete composite track beam-train interaction system are derived based on Lagrange's formulation. Validity of the model is verified by comparing the calculations with field-test data. The influence of the slip effect on the displacement amplitude of the track beam, vehicle acceleration and riding comfort is analyzed in detail. An interesting feature is that the graphic curves which reflect the dynamic responses of the steel-concrete composite beam-train interaction system under the influence of the slip can be divided into two regions (fluctuating area and smooth area), and there is an obvious critical value (0.8 × 10 6  N/m) between the two regions. When the connection stiffness reaches the critical value, the values of dynamic responses of the interaction system do not change anymore.